Analisis Implementasi Kurikulum Merdeka Terhadap Prestasi Belajar Siswa Kelas Iv Pada Pembelajaran Ipas Di Sdn 25 Mattirowalie - Sri Hartuti; Wahira; Amir Pada (PT PUSTAKA CENDEKIA GROUP, 2025)
This study aims to describe: 1) to analyze the implementation of the independent curriculum in science learning for Grade IV of SDN 25 Mattirowalie, 2) to analyze the obstacles and barriers in implementing the independent curriculum in science learning for Grade IV of SDN 25 Mattirowalie, 3) to analyze efforts to overcome obstacles and barriers in implementing the independent curriculum in science learning for Grade IV of SDN 25 Mattirowalie. This research is a qualitative research. The research was conducted at SDN 25 Mattirowalie in August 2024. The subjects of this study were the Principal, Grade IV Teachers, and Grade IV Students. Data collection techniques were carried out using observation, interviews and documentation. Activities in qualitative data analysis using interactive models are data collection, data reduction, data presentation, and conclusion drawing. The results of this study indicate that: 1) the implementation of the independent curriculum in science learning has been realized well, the planning carried out is by analyzing CP, compiling TP, and making ATP. The implementation of learning that has implemented differentiated learning that is adjusted to student needs and has compiled evaluations in the form of diagnostic assessments, formative and summative assessments, 2) there are obstacles and barriers such as less valid information, reference sources are still few, limited time in compiling teaching modules and assessments, 3) efforts made to overcome obstacles and barriers are by participating in seminars, webinars and workshops, increasing reference sources and utilizing the teaching module preparation guidebook provided by the government.